Visibilizar lo invisible - Vicente, María Castellanos (2019)
The aim of this article is to approach the work of the artist Ricardo O'Nascimento, focus¬ing in two of his works, where Ricardo researches about the electromagnetic waves and how to make them visible through their artistic practice. These concepts are formalized by the artist when creat¬ing wearables, installations and sculptures